SYNTHESIS AND REACTIONS OF 1-(4’-BROMOPHENACYL)-3-(4’-BROMO-PHENYL)-4,6-DIMETHOXYINDOLE - Jumina Jumina (Universitas Gadjah Mada, 2005)
1-Phenacyl-3-aryl-4,6-dimethoxyindoles 2b and 2c were obtained in good yields respectively through cyclization of N,N-diphenacylaniline 1b and 1c in trifluoroacetic acid. However, instead of giving pyrroloindole 3c, treatment of phenacylindole 2c with polyphosphoric acid afforded indolizine 5 in 42% yield. Phenacylindole 2c reacts with the Vilsmeier aroylation reagent consisted of a mixture of phosphoryl chloride and p-chloro-N,N-dimethylbenzamide to give 2-aroylindole 6 (32%) and pyrroloindole 7 (22%). When treated with sodium borohydride, phenacylindole 2c gave alcohol 8 in 83% yield. Nonetheless, treatment of alcohol 8 with either p-toluenesulfonic acid in glacial acetic acid or boron trifluoride etherate in benzene did not give the desired dihydropyrroloindole 12. Instead, the reactions afforded respectively acetyl ester 9 and indole 10 in 56% and 63% yield.